INFLUENCE OF LIFE SATISFACTION IN RESILIENCE OF PSCYHOLOGY STUDENT BREADWINNERS: A BASIS FOR SUPPPORT PROGRAM (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
Student breadwinners often struggle to juggle their academic duties alongside the financial demands of supporting their families. This dual responsibility frequently causes significant stress, exhaustion, and emotional pressure, highlighting the importance of resilience for their mental and emotional health. This research aims to explore how life satisfaction influences the resilience of student breadwinners, examining the various life factors that help them cope with hardships. Insights from this study can assist universities in creating better support mechanisms tailored to the needs of these students. This research utilized a quantitative approach, administering standardized surveys to 157 psychology students from first to fourth year. The surveys assessed life satisfaction across various domains—self, family, friends, school, and living environment—as well as resilience in facing adversity. Pearson’s correlation analysis revealed a strong positive relationship between life satisfaction and resilience (r = 0.99, p < 0.01). The results indicate that students who report greater satisfaction in their personal and social lives tend to possess higher resilience in overcoming academic and financial challenges. Life satisfaction among student breadwinners is primarily influenced by family and social support, academic experiences, and living conditions. Those with strong relationships and stable environments demonstrate greater resilience, while financial and academic pressures tend to lower satisfaction and coping abilities. Institutional support—including mental health services, financial aid, flexible policies, and peer programs—is essential to reduce stress, enhance well-being, and improve academic performance. Educational institutions must recognize and address the unique challenges faced by students who balance the roles of both learner and provider. This study highlights the vital importance of life satisfaction in strengthening the resilience of student breadwinners. The findings call for focused support within schools to enhance coping mechanisms and promote overall well-being. By addressing the distinct challenges faced by these students, the research provides a foundation for developing comprehensive interventions aimed at fostering both academic achievement and personal development. Moreover, by supporting policies and programs that enable student breadwinners to effectively manage their financial and academic responsibilities, this study contributes to the ongoing dialogue on educational equity and student support.
Keywords: student breadwinners; life satisfaction; resilience; academic challenges; financial responsibility; coping strategies; institutional support; educational equity